The role of connective interventions in the collective management of public-bad problems: Evidence from a socio-ecological system perspective - Galarza-Villamar, J.A.; McCampbell, M.; Agyekumhene, C.; Asingizwe, D.; Attoh, E.M.N.AN.; Damtew, E.; Chepkwony, R.; Cieslik, K.; Munthali, N.; Murindahabi, M.M.; Mutavi, Faith; Nyamekye, A.B.; et al. (Informa UK Limited, 2024)
Managing public-bad problems is difficult and arriving at an effective collective response can be an even bigger challenge. Using a socio-ecological systems framework, we explore the role of communication-focused interventions in the management of public bads in six African case-studies. We analyse case-specific livelihood units, public-bad risk conditions, and threats, and the strategies to prevent and control a public bad. We assess the impact of connective interventions on existing risk governance systems and problem management. Our findings show that connective interventions enable people to define risk boundaries, learn about the costs and benefits of public-bad management, and develop capacity for collective decision-making and problem monitoring. However, connective interventions cannot work in isolation and require complementary strategies, and trust in broader governance and institutional arrangements. Our research demonstrates the value of the social ecological systems framework in synthesizing lessons and insights from diverse interdisciplinary studies.